Fingerprint-free tracking with dynamic enhanced field division - Zhang, Qingquan; Zhou, Ziqiao; Xu, Wei; Qi, Jing; Guo, Chenxi; Yi, Ping; Zhu, Ting; Xiao, Sheng (2015 International Conference on Computer Communications, 2015)
Wireless sensor networks are often deployed for tracking moving objects. Many tracking algorithms have been proposed with two general assumptions: the preset fingerprints(prior landmark or context information) and an interference-free environment. These algorithms, however, cannot be used for on-demand deployment where finger-prints are unavailable and would perform poorly in interference-rich environments. In this paper, we present a fingerprint-free localizing and tracking algorithm, called Enhanced Field Division (EFD). The EFD algorithm is used to dynamically divide the field into areas with unique signatures and tracks the target, without any finger-prints. We also implemented a proof-of-concept localization platform to demonstrate the tracking accuracy and the algorithm performance in practical, interference rich environment.